2014
DOI: 10.1007/s00436-014-3936-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel cathepsin B and cathepsin B-like cysteine protease of Naegleria fowleri excretory–secretory proteins and their biochemical properties

Abstract: Naegleria fowleri causes a lethal primary amoebic meningoencephalitis (PAM) in humans and experimental animals, which leads to death within 7-14 days. Cysteine proteases of parasites play key roles in nutrient uptake, excystment/encystment, host tissue invasion, and immune evasion. In this study, we cloned N. fowleri cathepsin B (nfcpb) and cathepsin B-like (nfcpb-L) genes from our cDNA library of N. fowleri. The full-length sequences of genes were 1,038 and 939 bp (encoded 345 and 313 amino acids), and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…The important components of the N. fowleri ESP are the cysteine protease named N. fowleri cathepsin B‐like (nfcpb‐L) and cathepsin B (nfcpb), the study indicated that these refolding proteins have a principal role in host immune evasion, tissue invasion, nutrient uptake, and encystment/excystment. Both rNfCP‐B and rNfCPB‐L have shown proteolytic activity for several proteins including IgA, IgG, IgM, fibronectin, haemoglobin, albumin and collagen . Further, it was recently evaluated that N. fowleri excretory and secretory proteins (NfESP) were involved in producing inflammatory responses in BV‐2 microglial cells.…”
Section: Naegleria Fowleri and Host Immune Responsementioning
confidence: 99%
“…The important components of the N. fowleri ESP are the cysteine protease named N. fowleri cathepsin B‐like (nfcpb‐L) and cathepsin B (nfcpb), the study indicated that these refolding proteins have a principal role in host immune evasion, tissue invasion, nutrient uptake, and encystment/excystment. Both rNfCP‐B and rNfCPB‐L have shown proteolytic activity for several proteins including IgA, IgG, IgM, fibronectin, haemoglobin, albumin and collagen . Further, it was recently evaluated that N. fowleri excretory and secretory proteins (NfESP) were involved in producing inflammatory responses in BV‐2 microglial cells.…”
Section: Naegleria Fowleri and Host Immune Responsementioning
confidence: 99%
“…RAAS activation underlies numerous pathologies [20]. Cathepsin B from amoeba can cleave several human proteins including immunoglobulins (IgA, IgG, IgM), hemoglobin, collagen, fibronectin, and albumin [21]. Cathepsin D cleaves fibronectin and laminin.…”
Section: Types Of Cathepsins and Their Functional Specificitiesmentioning
confidence: 99%
“…Finally, the resistant form of N. fowleri, the cyst, is usually spherical, smooth, double walled and refractive, and measures approximately 20 µm in diameter (Fig. 2c); the wall is composed mainly of polysaccharides (Ch avez- Munguía et al, 2009;Lee et al, 2014). The cysts contain pores that are sealed by a thin mucoid layer.…”
Section: Ecology and Morphologymentioning
confidence: 99%
“…Recently, cathepsin B and cathepsin-B-like cysteine proteases have been cloned and purified. These proteases can degrade a variety of human substrates, such as IgA, IgG, IgM, collagen, fibronectin, haemoglobin and albumin (Lee et al, 2014). Considering all of these findings, the proteases of N. fowleri might be excellent targets of chemotherapeutic agents directed against this pathogen (Klemba & Goldberg, 2002;Sajid & McKerrow, 2002;McKerrow et al, 2008).…”
Section: Mechanisms Of Pathogenicitymentioning
confidence: 99%